2013
DOI: 10.1128/mcb.00473-13
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin-Interacting Protein 1 Phosphorylation by Receptor Tyrosine Kinases

Abstract: b Huntingtin-interacting protein 1 (HIP1) binds inositol lipids, clathrin, actin, and receptor tyrosine kinases (RTKs). HIP1 is elevated in many tumors, and its expression is prognostic in prostate cancer. HIP1 overexpression increases levels of the RTK epidermal growth factor receptor (EGFR) and transforms fibroblasts. Here we report that HIP1 is tyrosine phosphorylated in the presence of EGFR and platelet-derived growth factor ␤ receptor (PDGF␤R) as well as the oncogenic derivatives EGFRvIII, HIP1/ PDGF␤R (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Knockdown of Dab2 accelerates the internalization rate of TLR4 and increases the amount of internalized TLR4 following stimulation of macrophages by LPS. The concept of a “clathrin sponge” has been proposed previously on the basis of the findings that huntingtin-interacting protein 1, which specifically binds clathrin, sequesters clathrin and acts as a clathrin sponge to prevent endocytosis of activated receptor tyrosine kinases to form endosomes in cancers 60 . Dab2 interacts with clathrin, and the interaction is diminished during mitosis, causing an increased internalization of the YXXØ type endocytic cargos 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Dab2 accelerates the internalization rate of TLR4 and increases the amount of internalized TLR4 following stimulation of macrophages by LPS. The concept of a “clathrin sponge” has been proposed previously on the basis of the findings that huntingtin-interacting protein 1, which specifically binds clathrin, sequesters clathrin and acts as a clathrin sponge to prevent endocytosis of activated receptor tyrosine kinases to form endosomes in cancers 60 . Dab2 interacts with clathrin, and the interaction is diminished during mitosis, causing an increased internalization of the YXXØ type endocytic cargos 59 .…”
Section: Discussionmentioning
confidence: 99%
“…100 μg of total protein was electrophoresed on 6% SDS-PAGE gels, and transferred to a PVDF membrane. Proteins were detected with anti-Brca1 antiserum (1:100; GH118, kind gift of Dr. Jos Jonkers), mouse monoclonal anti-Hip1 (1:1000; 1B11, Ross laboratory (Ames et al, 2013)) and rabbit polyclonal anti-γH2AX (1:1000, Cell Signaling). Blots were developed with Supersignal West Pico chemiluminescence substrate (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…As four tyrosines in the human HIP1 ortholog were previously reported to be phosphorylated by the receptor tyrosine kinase epidermal growth factor receptor ( 23 ) and this phosphorylation was important for cell survival, we investigated whether phosphorylation of the analogous tyrosines in C. elegans HIPR-1 affects Orsay virus infection. As three of these tyrosines were conserved in HIPR-1, we engineered a triple tyrosine-to-phenylalanine (Y-F) nonphosphorylatable mutant form of HIPR-1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mice deficient in both HIP1 and HIP1R exhibited aggravated spinal abnormalities and dwarfism, suggesting existence of a compensatory role of HIP1 and HIP1R ( 21 ). HIP proteins may be more functionally diverse than previously described, as studies in human cell culture have also suggested human HIP proteins may play a role in other cellular pathways such as androgen receptor transcription and apoptosis ( 22 , 23 ). Only a few studies have investigated the potential role of mammalian HIP1 and HIP1R in virus infection ( 24 26 ).…”
mentioning
confidence: 95%